2012
DOI: 10.1029/2011gb004098
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the terrestrial weathering feedback for multimillennial coral reef habitat recovery

Abstract: [1] Modern-day coral reefs have well defined environmental envelopes for light, sea surface temperature (SST) and seawater aragonite saturation state (W arag ). We examine the changes in global coral reef habitat on multimillennial timescales with regard to SST and W arag using a climate model including a three-dimensional ocean general circulation model, a fully coupled carbon cycle, and six different parameterizations for continental weathering (the UVic Earth System Climate Model). The model is forced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 101 publications
(157 reference statements)
5
65
1
Order By: Relevance
“…My results suggest a longer lifetime of human-induced future warming than previous studies (15,(38)(39)(40)(41) (Fig. 2B).…”
Section: Resultscontrasting
confidence: 55%
“…My results suggest a longer lifetime of human-induced future warming than previous studies (15,(38)(39)(40)(41) (Fig. 2B).…”
Section: Resultscontrasting
confidence: 55%
“…Solar insolation at the top of the atmosphere, wind stress, and wind fields varied seasonally (Kalnay et al, 1996), and the wind fields were geostrophically adjusted to air temperature anomalies (Weaver et al, 2001). The sediment and weathering models (Meissner et al, 2012) were not used. Model equilibration was achieved by integrating over 10 000 years prior to application of climate forcing.…”
Section: Methodsmentioning
confidence: 99%
“…This effectively suppresses the long-term negative feedback mechanism by preventing the weathering rate from adapting to changes in environmental factors such as temperature and atmospheric CO 2 concentration. Meissner et al (2012) replaced the standard parameterization of weathering in the UVic ESCM with a number of adaptations from previous carbon-cycle box-models (see "Methods" section) to introduce and investigate the weathering negative feedback mechanism in the context of future climate change scenarios. They found that the long-term climate response to various emission scenarios depends almost exclusively on the total amount of CO 2 released, regardless of the rate at which it is being emitted, and that carbon uptake through an increase in terrestrial weathering has a significant effect on the climate system.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Using a similar approach as Meissner et al (2012), we introduced a set of box-model parameterizations of terrestrial weathering to examine potential impacts on the carbon cycle as weathering rates adjust to the increase in temperature and atmospheric CO 2 levels during the latest deglacial period. These weathering schemes were adapted from Berner (1994), Lenton and Britton (2006), and Uchikawa and Zeebe (2008), and a full description of their implementation into the UVic ESCM is given by Meissner et al (2012).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation